Roles and molecular mechanisms of EMILIN-1 in physiology and disease: a narrative review - Yaoxin Wang; Huan Zang; Yuqing Huang; Zhongfeng Wang; Xiaomei Wang (Frontiers in Medicine, 2026)
Elastin microfibril interface located protein 1 (EMILIN-1) is a homotrimeric glycoprotein of the extracellular matrix (ECM) family that participates in ECM organization and regulates cell signaling. It is critical for maintaining tissue homeostasis, intercellular communication, and modulation of pathological microenvironments. Accumulating evidence indicates that the development and progression of various human diseases, including chronic inflammatory diseases, lymphatic diseases, and cancers, are closely associated with abnormal expression or dysfunction of EMILIN-1. Remarkably, the biological effects of EMILIN-1 are highly context dependent and cell type dependent. EMILIN-1 acts as a well-recognized tumor suppressor in malignancies such as head and neck squamous cell carcinoma and breast cancer, yet it promotes lymphatic disease progression through modulation of transforming growth factor β (TGF-β) signaling. This review summarizes the molecular structural characteristics, physiological functions, and major regulatory pathways of EMILIN-1, with particular emphasis on functional heterogeneity and the underlying mechanisms across diverse diseases. We also highlight recent advances in clinical translation, followed by a discussion of current research bottlenecks and prospective directions. These insights establish a theoretical framework for developing diagnostic biomarkers and optimizing targeted therapeutic strategies.